2007
DOI: 10.1007/s10509-007-9623-4
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Bianchi type-I models with constant deceleration parameter in general relativity

Abstract: A special law of variation for Hubble's parameter is presented in a spatially homogeneous and anisotropic Bianchi type-I space-time that yields a constant value of deceleration parameter. Using the law of variation for Hubble's parameter, exact solutions of Einstein's field equations are obtained for Bianchi-I space-time filled with perfect fluid in two different cases where the universe exhibits powerlaw and exponential expansion. It is found that the solutions are consistent with the recent observations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 36 publications
8
88
1
Order By: Relevance
“…It is observed that the above anisotropy parameter of the expansion is equivalent to the ones obtained for exponential expansion in Bianchi type-I [51] and Bianchi type-V [52,53] cosmological models with isotropic fluid and is exactly same for exponential expansion in Bianchi type-III [54] for anisotropic fluid.…”
Section: Model For Exponential Expansionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is observed that the above anisotropy parameter of the expansion is equivalent to the ones obtained for exponential expansion in Bianchi type-I [51] and Bianchi type-V [52,53] cosmological models with isotropic fluid and is exactly same for exponential expansion in Bianchi type-III [54] for anisotropic fluid.…”
Section: Model For Exponential Expansionsupporting
confidence: 61%
“…By using equation (15) in equation (13), we obtain the reduced form of the anisotropy parameter of the expansion as (17) It is observed that the above anisotropy parameter of the expansion is equivalent to the ones obtained for exponential expansion in Bianchi type-I [51] and Bianchi type-V [52,53] cosmological models with isotropic fluid and is exactly same for exponential expansion in Bianchi type-III [54] for anisotropic fluid. The difference between the expansion rates on and is reduced to…”
Section: Isotropization and The Solutionmentioning
confidence: 82%
“…Singh et al [32] have studied flat FRW and Bianchi type models by using the special law of Hubble parameter that yields constant value of deceleration parameter. A similar law of variation for the Hubble parameter in anisotropic space-time metrics that yields a constant value of the deceleration parameter, and generated solutions for Bianchi Type-I [33], LRS Bianchi Type-II [11,34], Bianchi Type-V metric in General Relativity have been proposed .…”
Section: Solution Of Field Equationsmentioning
confidence: 91%
“…Some new exact solutions of Einstein's field equations emerged in a spatially homogeneous and anisotropic Bianchi type-V space-time with minimally interacting perfect fluid and anisotropic DE components, which has dynamic EoS parameter investigated by Pradhan et al [10]. A special law of variation for Hubble's parameter is presented by S.Kumar & C.P.Singh [11] …”
Section: Introductionmentioning
confidence: 99%
“…the Bianchi Type I (BI) universe has been studied by several researchers to discuss the effect of anisotropy in several contexts. Kumar and Singh [37,38] have studied the exact solutions for the Bianchi Type I universe in various theories. Sharif and Waheed [39] investigated exact solutions for anisotropic fluid by considering the LRS Bianchi type-I universe which generalizes the flat FRW universe in the modified theory.…”
Section: Introductionmentioning
confidence: 99%